2017
DOI: 10.1002/aoc.3712
|View full text |Cite
|
Sign up to set email alerts
|

Review: Quantitative structure–activity/property relationships as related to organotin chemistry

Abstract: The aim of this review is to examine the current status of quantitative structure–activity/property relationships (QSAR/QSPR) as related to organotin chemistry. QSAR/QSPR are mathematical models that relate some measurable biological activity or physical property in a series of similar compounds to a descriptor or descriptors associated with the molecules. Descriptors used in QSAR/QSPR studies are endless, from traditional parameters to newly developed ones. They range from quantum chemical descriptors to phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Organotin compounds have been widely used in organic synthesis, catalysis, materials, and medicinal/biocidal aspects (Davies et al, 2008). Organotin complexes with carboxylate ligands have attracted a lot of attention because they display higher catalytic and cytotoxic activity and the diversified structures (Arjmand et al, 2014;Bantia et al 2019;Davies et al, 2008;Eng, 2017;Tian et al, 2019). Some organotin complexes of N-salicylidene-Lvaline have been synthesized, and displayed good optical and biological properties (Beltran et al, 2003;Rivera et al, 2006;Tian et al, 2005Tian et al, , 2016Tian et al, , 2018Yao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organotin compounds have been widely used in organic synthesis, catalysis, materials, and medicinal/biocidal aspects (Davies et al, 2008). Organotin complexes with carboxylate ligands have attracted a lot of attention because they display higher catalytic and cytotoxic activity and the diversified structures (Arjmand et al, 2014;Bantia et al 2019;Davies et al, 2008;Eng, 2017;Tian et al, 2019). Some organotin complexes of N-salicylidene-Lvaline have been synthesized, and displayed good optical and biological properties (Beltran et al, 2003;Rivera et al, 2006;Tian et al, 2005Tian et al, , 2016Tian et al, , 2018Yao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] It has been observed that the number and nature of the organic groups bound to the tin centre and the carboxylate ligand appear to play an important role in determining their anti-tumour activity. [4][5][6][7] To design and synthesize new organotin carboxylates by selecting carboxylic ligands and organotin substrates has been encouraged in order to achieve efficacy. N-Salicylidene-α-amino acid, derived from L-αamino acid and salicylaldehyde, is a versatile chiral carboxylic ligand having the hydroxyl, imine, and carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atoms are omitted for clarity The 2-D supramolecular network of 5 by the intermolecular O-H⋅⋅⋅O hydrogen bonds; phenyls bound to tins and hydrogen atoms except OH are omitted for clarity bipyramid, where two methyl groups adopt axial positions (C(1)-Sn(1)-C(2) 156.87 (14)°) and the equatorial positions are occupied by the phenolic O(1) atom, one carboxylate O(2) atom and the imino N(1) atom of the ligand, and the phenolic O(1A) atom and ether O(4A) atom of the adjacent ligand. Tin atom forms one four-, two five-and one six-membered chelate ring, and the corresponding bite angle is 74.05(7) (O(1)-Sn(1)-O(1A)), 57.75(6) (O(1A)-Sn(1)-O(4A)), 73.47(8) (O(2)-Sn(1)-N(1)), 81.73(8)°(O(1)-Sn(1)-N(1)), respectively.Inthis entrosymmetric dimmers, there exist a (R)-and a (S)-isomers, and two dimeric units are linked by a pair of intermolecular O-H⋅⋅⋅O hydrogen bonds between the phenolic hydroxyl O(5)-H(5) and uncoordinated carbonyl O(3) i atom (symmetry code i = x, y, z + 1) to form a onedimensional supramolecular double-chain in which there is a centrosymmetric R 2 2 (30) macrocycle with Sn⋅⋅⋅Sn distances of 9.82(2) Å (Table 4, Figure 2). The structures of complexes 2 and 3 are similar to that of 1 and are both the centrosymmetric weak dimers (see supporting information, Figures S1 and S2) with the long Sn(1)⋅⋅⋅O(1A) (symmetry operation A = −x + 1, −y, −z + 2 for 2 and -x + 1, −y + 1, −z for 3) (3.3414 (17) Å for 2, 3.2789 (19) Å for 3) and Sn(1)⋅⋅⋅O(4A) (3.0665 (18) Å for 2, 3.085(2) Å for 3) from phenolic O(1) and ether O(4) of the adjacent ligand, respectively.…”
mentioning
confidence: 99%